2022
DOI: 10.1007/s00423-022-02465-0
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted techniques in vascular and endovascular surgery

Abstract: For thousands of years, robots have inspired the imagination of humans, but it was only about 35 years ago that a robot was used for the first time in medicine. Since then, robot-assisted procedures have become increasingly popular in urology, general surgical specialties, and gynecology. Robot-assisted vascular surgery was first introduced in 2002 and was thought to overcome the limitations of laparoscopy. However, it did not gain widespread popularity, and its usage is still limited to a few centers worldwid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Since then, two advanced robotic surgical systems have been mainly used in laparoscopic vascular surgery: the da Vinci (Intuitive Surgical Inc, Mountain View, Calif) and Zeus (Computer Motion Inc, Santa Barbara, Calif) systems, which are Leader-Follower robots with similar capabilities (10). The production of the Zeus robot has been discontinued, while in the last decade, the da Vinci robotic surgical telemanipulator has been used for several vascular procedures, that, according to a recent literature review (8), include: robotically assisted repair of abdominal aortic aneurysms (AAA), thromboendarterectomy of the aorta and pelvic artery, iliofemoral and aortofemoral bypass, thoracofemoral bypass from descending thoracic aorta, splenic artery aneurysm, renal artery reconstruction, robotic treatment of type II endoleak after endovascular aneurysm repair, robotic surgery for celiac artery compression syndrome, and robotic-assisted central venous reconstruction.…”
Section: Robot-assisted Laparoscopic Vascular Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…Since then, two advanced robotic surgical systems have been mainly used in laparoscopic vascular surgery: the da Vinci (Intuitive Surgical Inc, Mountain View, Calif) and Zeus (Computer Motion Inc, Santa Barbara, Calif) systems, which are Leader-Follower robots with similar capabilities (10). The production of the Zeus robot has been discontinued, while in the last decade, the da Vinci robotic surgical telemanipulator has been used for several vascular procedures, that, according to a recent literature review (8), include: robotically assisted repair of abdominal aortic aneurysms (AAA), thromboendarterectomy of the aorta and pelvic artery, iliofemoral and aortofemoral bypass, thoracofemoral bypass from descending thoracic aorta, splenic artery aneurysm, renal artery reconstruction, robotic treatment of type II endoleak after endovascular aneurysm repair, robotic surgery for celiac artery compression syndrome, and robotic-assisted central venous reconstruction.…”
Section: Robot-assisted Laparoscopic Vascular Surgerymentioning
confidence: 99%
“…However, to date, data from the existing literature are limited to drawing a conclusion regarding the efficacy of robotic technology in vascular surgery (10), given that most studies are mainly limited to individual cases (Stadler's group, which reported on a series of 285 procedures (33), is an exception). At present, robot-assisted vascular surgery has not achieved great popularity and its use is still limited to a few centers worldwide.…”
Section: Robot-assisted Laparoscopic Vascular Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…The ultra-high dexterity makes the continuum robot widely used in various fields of medicine such as laparoscopy and thoracoscopy [5][6][7]. However, with the development of minimally invasive surgery, the requirements for surgical instruments have become stricter.…”
Section: Introductionmentioning
confidence: 99%